Type V Secretion in Gram-Negative Bacteria - Bernstein, Harris D. (EcoSal Plus, 2019)
Type V, or “autotransporter,” secretion is a term used to refer to several simple protein export pathways that are found in a wide range of Gram-negative bacteria. Autotransporters are generally single polypeptides that consist of an extracellular (“passenger”) domain and a β barrel domain that anchors the protein to the outer membrane (OM). Although it was originally proposed that the passenger domain is secreted through a channel formed solely by the covalently linked β barrel domain, experiments performed primarily on the type Va, or “classical,” autotransporter pathway have challenged this hypothesis. Several lines of evidence strongly suggest that both the secretion of the passenger domain and the membrane integration of the β barrel domain are catalyzed by the barrel assembly machinery (Bam) complex, a conserved hetero-oligomer that plays an essential role in the assembly of most integral OM proteins. The secretion reaction appears to be driven at least in part by the folding of the passenger domain in the extracellular space. Although many aspects of autotransporter biogenesis remain to be elucidated, it will be especially interesting to determine whether the different classes of proteins that fall under the type V rubric—most of which have not been examined in detail—are assembled by the same basic mechanism as classical autotransporters.